2019
DOI: 10.3835/plantgenome2017.09.0081
|View full text |Cite
|
Sign up to set email alerts
|

RicetissueTFDB: A Genome‐Wide Identification of Tissue‐Specific Transcription Factors in Rice

Abstract: Core Ideas Validated TFs expressed in rice tissue types to study gene expression profiles in rice tissues. Tissue‐specific TFs were analyzed in different rice tissues. RicetissueTFDB integrates tissue expression characters, genomic location, and GO terms for TFs. Transcription factors (TFs) regulate plant gene expression in different tissues. To investigate TF genes in rice (Oryza sativa L.), a genome‐wide TF identification was conducted with the japonica rice genome. This study identified 3078 putative TFs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…According to the top three most significantly enriched motifs, we found that the motifs for the binding of bHLH and C2H2 transcription factors (TFs) were more enriched in PDS-specific IP-G4s + ; in contrast, the motifs for the binding of BBRBPC and bZIP TFs were more enriched in PEG-specific IP-G4s + ( Figure 2 E). These TFs have been reported to play crucial roles in the regulation of plant growth and development and stress responses [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the top three most significantly enriched motifs, we found that the motifs for the binding of bHLH and C2H2 transcription factors (TFs) were more enriched in PDS-specific IP-G4s + ; in contrast, the motifs for the binding of BBRBPC and bZIP TFs were more enriched in PEG-specific IP-G4s + ( Figure 2 E). These TFs have been reported to play crucial roles in the regulation of plant growth and development and stress responses [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In rice, the major TF families that regulate salt tolerance are well studied. These include dehydration-responsive element (DRE) binding protein (DREB), ABA-responsive element (ABRE) binding protein/factor (AREB/ABF), and NAC (NAM, ATAF1/2, CUC2) [78]. Increasing research supports the role of NAC in plant response to environmental stress conditions, including salt stress [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…MYB-related transcription factors comprise a prominent subtype of MYB superfamily in plants (Du et al, 2013). Based on the previous research, there are 64, and 223 MYB-related genes in the model plant Arabidopsis and rice, respectively (Chen et al, 2006(Chen et al, , 2019. Recently, 62 genes in Physcomitrella patens (Pu et al, 2020), 138 genes in Solanum tuberosum (Liu Y. H. et al, 2020), 73 genes in Musa acuminate, and 59 genes in Musa balbisiana (Tan et al, 2020) were identified as MYB-related genes.…”
Section: Discussionmentioning
confidence: 99%